NIAT SEBAGAI VARIABEL INTERVENING MEMPENGARUHI SIKAP, KONTROL PERILAKU DAN TAHUN PEMBINAAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus UMKM Di Wilayah Kantor Pelayanan Pajak Semarang Barat) - Siti Purwaningsih, 12.05.52.0222; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2016)
This study aimed to analyze the influence of taxpayer attitudes, perceived behavioral control and guidance of taxpayers on tax compliance intentions as an intervening variable. The population in this study is an individual taxpayer SMEs do business in the West Semarang Primary Office 2015 to February 2016 amounted to 68 301 taxpayers. Sampling was done by using purposive sampling method and the total sample of 118 respondents. Primary data collection method used is the questionnaire. And data analysis using multiple linear regression model. The results showed that the taxpayer attitudes and perceived behavioral control positive influence on the intention to comply, while the taxpayer attitudes, perceived behavioral control, in coaching the taxpayer and the intention to comply also have a positive effect on tax compliance.Keywords: Attitudes Taxpayer, Perceived Behavioral Control, In Coaching The Taxpayer, The Intention To Obey, Tax Compliance